1987
DOI: 10.1029/ja092ia12p13485
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field drift shell splitting: Cause of unusual dayside particle pitch angle distributions during storms and substorms

Abstract: We present a magnetic field drift shell‐splitting model for the unusual butterfly and head‐and‐shoulder energetic (E > 25 keV) particle pitch angle distributions (PADs) which appear deep within the dayside magnetosphere during the course of storms and substorms. Drift shell splitting separates the high and low pitch angle particles in nightside injections as they move to the dayside magnetosphere, so that the higher pitch angle particles move radially away from Earth. Consequently, butterfly PADs with a surplu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
158
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(168 citation statements)
references
References 52 publications
9
158
0
1
Order By: Relevance
“…Early surveys of energetic electrons consistently found pancake distributions inside 6-9 R E (1 R E = 6370 km), while butterfly or isotropic distributions appeared outside [e.g., West et al, 1973;Lyons and Williams, 1975]. The trapping distributions of the inner magnetosphere largely result from inward diffusion that preserves the first and second adiabatic invariants [e.g., Schulz and Lanzerotti, 1974], while the butterfly distributions in the outer magnetosphere were explained largely as effects of magnetic drift shell splitting or the negative gradient in the radial flux, possibly in combination with wave-particle scattering and often during disturbed conditions [e.g., Roederer, 1970;Lyons and Williams, 1975;Sibeck et al, 1987;Horne et al, 2003]. Both unidirectional and bidirectional distributions of energetic electrons were commonly observed in the magnetotail and associated with acceleration events in the magnetotail plasma sheet as well as open/closed field topology [e.g., Stone, 1976, 1977].…”
Section: Introductionmentioning
confidence: 99%
“…Early surveys of energetic electrons consistently found pancake distributions inside 6-9 R E (1 R E = 6370 km), while butterfly or isotropic distributions appeared outside [e.g., West et al, 1973;Lyons and Williams, 1975]. The trapping distributions of the inner magnetosphere largely result from inward diffusion that preserves the first and second adiabatic invariants [e.g., Schulz and Lanzerotti, 1974], while the butterfly distributions in the outer magnetosphere were explained largely as effects of magnetic drift shell splitting or the negative gradient in the radial flux, possibly in combination with wave-particle scattering and often during disturbed conditions [e.g., Roederer, 1970;Lyons and Williams, 1975;Sibeck et al, 1987;Horne et al, 2003]. Both unidirectional and bidirectional distributions of energetic electrons were commonly observed in the magnetotail and associated with acceleration events in the magnetotail plasma sheet as well as open/closed field topology [e.g., Stone, 1976, 1977].…”
Section: Introductionmentioning
confidence: 99%
“…Those energetic ions and electrons could be injected at local midnight and drift toward the dayside. Due to drift shell splitting, ring current ion fluxes with an anisotropic pitch angle distribution are enhanced in the afternoon sector (Sibeck et al, 1987). With density enhancements of cold ions, the anisotropic RC proton distributions can become unstable so as to easily excite EMIC waves (Gary et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Kosik (1979) reported that during a magnetically quiet period the convection electric field is very weak and the magnetic field asymmetry produces the dominant effect. Sibeck et al (1987) further showed that compared to gradient and curvature drifts the electric drifts are negligible for the >25 keV particles. Therefore, for the present particle trajectory traces, an E=0 electric field was assumed along with the T96 model.…”
Section: Trajectory Generatormentioning
confidence: 99%
“…These butterfly distributions were caused by the Russian high-altitude nuclear detonation on 28 October 1962. Various reasons for the natural occurrence of butterfly distributions have been given in literature; such as drift shell splitting (Roederer, 1967(Roederer, , 1970 and either magnetopause shadowing (West et al, 1972(West et al, , 1973 or a negative radial flux gradient (Pfitzer et al, 1969;Sibeck et al, 1987).…”
Section: Introductionmentioning
confidence: 99%